THE RECONSTRUCTION OF THE RAT TONGUE HEMOMICROCIRCULATORY STREAM IN THE DYNAMICS OF EXPERIMENTAL DIABETES MELLITUS - Sultan, R.Y.; Pokotylo, P.B.; Hnidyk, Y.V.; Mota, O.M.; Halyuk, U.M. (World of Medicine and Biology, 2016)
The aim of the work was to determine the of features of tongue’s hemomicrocirculatory bed of white rat in norm and in the dynamics of the flow of experimental diabetes. To achieve the goal we have the following morphological techniques were used: preparation of the rats tongue, modeling of streptozotocin-induced diabetes, vascular injection of rat’s tongue vessels, manufacturing and bleaching of tongues preparations, morphometry of vascular structures, statistical processing of morphometric parameters and biochemical study of peripheral blood. New data on the restructuring tongue’s hemomicrocirculatory bed of white rats in the dynamics of the flow of experimental diabetes.